Prevalence and associations of the three-layer sign in age-related macular degeneration: the Beijing eye study - Jonas, Jost B.; Panda-Jonas, Songhomitra; Xu, Jie; Jonas, Rahul A.; Wang, Ya Xing (Acta ophthalmologica, 2025)
Objective To assess the prevalence and associations of the detectability of the three-layer sign (TLS) in a general population, including individuals with age-related macular degeneration (AMD) or without any retinal disease. Methods Using OCT images running horizontally through the foveola of participants of the population-based Beijing Eye Study, we assessed the TLS detectability. We defined the TLS as the visibility of the ellipsoid zone (EZ), interdigitation zone and retinal pigment epithelium (RPE)/Bruch's membrane line as separate units in the foveola on optical coherence tomographic (OCT) images. Results The study included 1566 eyes (age: 65.3 ± 9.8 years; axial length: 23.01 ± 0.93 mm; range: 19.90 mm-28.93 mm), randomly selected within each group of normal eyes (n = 592; 37.8%), eyes with early AMD (n = 700; 44.7%), intermediate AMD (n = 267; 17.0%), and late AMD (n = 7; 0.4%). In the normal group, TLS prevalence decreased with older age (OR: 0.93; p < 0.001), declining from 217/265 (81.9%) in the 50-59 years age group to 57/126 (45.2%) in individuals aged 70+ years. In the whole study cohort, TLS prevalence decreased (p < 0.001) from 389/592 (65.7%) in the normal group to 334/700 (47.7%), 66/267 (24.7%) and 0/7 (0%) in early AMD, intermediate AMD and late AMD, respectively. In multivariable analysis, higher TLS prevalence was associated with younger age (OR: 0.92; p < 0.001), female sex (OR: 1.65; p < 0.001), lower AMD stage (OR: 0.51; p < 0.001), better best-corrected visual acuity (OR: 0.42; p = 0.03), and lower prevalence of a flat retinal pigment epithelium elevation (OR: 0.68; p = 0.04). Conclusions The foveal TLS may be taken as a qualitative sign of the intactness of the deep layers of the fovea, with its prevalence decreasing with older age, higher AMD stage and worse best-corrected visual acuity.
Gesehen am 05.02.2025